Investigation of mechanical properties of Ruddlesden-Popper 2D,2D-3D and 3D perovskites using an experimental and first principles approach - Rathore, Sudharm (Nanyang Technological University, 2023)
Hybrid organic-inorganic perovskites (HOIPs) are considered as one of the most promising candidates for the photovoltaic application. Although a lot of research has been done for the improvement in efficiency and stability of the devices made from this material, the mechanical property study of these materials is very limited. The mechanical properties of hybrid organic inorganic perovskites crystals have been mentioned in a few reports. However, it is also important to study the mechanical properties of the perovskite’s thin films, especially those used in flexible devices, since their polycrystalline nature makes them different from single crystals. The stiffness of the perovskite active layer plays a critical role in influencing the flexibility of a solar cell. This is one of the important parameters which must be considered while deciding the architecture of the flexible device. In this study, we report for the very first time, the elastic modulus of the most commonly used 3D perovskite, i.e., methylammonium lead iodide (MAPbI3), the pure 2D perovskite (5-AVA)2PbI4 which is based on 5-aminovaleric acid (5-AVA) cation as well as the 2D-3D mixed perovskites thin films through nanoindentation technique. The experimental results have also been corroborated by density functional theory calculations done for the 2D and 3D perovskite. The 2D perovskite shows a much lower modulus than the 3D perovskite and can be used within a 2D-3D mixture to improve the mechanical flexibility of the active layer. Also, it is well established that 2D perovskites are much more stable against moisture as compared to their 3D counterparts due to the presence of hydrophobic organic alkyl ammonium cation. Thus, the device containing an active layer comprising a mixture of 3D and 2D perovskite can be used to improve the environmental stability of the overall device in addition to achieving mechanical durability. We have also investigated the effect of the number of inorganic layers ‘n’ on the elastic modulus of 2D, quasi-2D perovskites and 3D perovskite based on butylammonium cation (BA)2PbI4 and MAPbI3 thin films using nanoindentation technique. Our studies indicate the role of the orientation of the inorganic layers in perovskite films in tailoring their mechanical response. The experimental results have been substantiated using first principal density functional theory (DFT) calculations. We also report other important mechanical parameters, namely, shear modulus, bulk modulus, Poisson’s ratio, Pugh’s ratio, Vickers hardness, yield strength and the universal elastic anisotropic index using DFT simulations. Anisotropy is observed in the elastic modulus of the materials under study and has been discussed in detail in the manuscript. Understanding the mechanical behavior of 2D Ruddlesden Popper perovskite thin film in comparison with conventional 3D perovskite offers intriguing insights into the atomic layer dependent properties and paves the path for next generation mechanically durable and novel devices. The present study also includes the measurement of the elastic modulus of the 3D perovskite, i.e., methylammonium lead iodide (MAPbI3), 2D perovskite, based on phenylethylammonium [(PEA)2PbI4] and mixed 2D-3D perovskite thin film using nanoindentation technique. First principles density functional theory (DFT) calculations done as part of the current work on pure 3D and 2D perovskites also corroborate our experimental results. The effect of the 2D-3D mixture on the elastic modulus has also been investigated, and it has been found that the modulus values increase with the increase in the percentage of 3D perovskite within the 2D-3D perovskite mixture. Moreover, a change in the volume fraction of PEA in the 2D-3D mixed perovskite results in a mixture of quasi-2D perovskite in different proportions within the mixed perovskite. The knowledge gained by comparing DFT and experimental methodologies allows for the logical design of multilayer HOIPs with mechanical properties that are suitable for strain-intensive and flexible optoelectronic applications. In addition to the static mechanical properties, we have also investigated the rate-dependent inelastic mechanical behaviour in bulk crystals of lead–halide 2D, quasi-2D and 3D perovskites using nanoindentation creep and stress relaxation measurements at different loading rates. The mechanical response of these materials to dynamic strain must be understood to successfully use them in deformable devices. In the current study, a range of perovskites: CH3NH3PbI3 (3D) perovskite, (BA) butylammonium based 2D perovskite (CH3(CH2)3NH3)2PbI4, BA based quasi-2D perovskite (CH3(CH2)3NH3)2(CH3NH3)Pb2I7, (PEA)phenylethylammonium based 2D perovskite (C6H5(CH2)2NH3)2PbI4, and PEA based quasi-2D perovskite (C6H5(CH2)2NH3)2(CH3NH3)Pb2I7 have been fabricated with particle sizes ranging in 5-10nm as found using TEM. The nanoindentation creep and stress relaxation experiments prove the time and rate-dependent mechanical properties of this 2D, quasi-2D, and 3D HOIPs crystal though varying in their magnitudes. We observe that the 3D, as well as BA based perovskite samples, show strain rate sensitivity, whereas PEA based perovskite samples were relatively insensitive towards the rate of loading. Propagation and interaction of dislocation is much more difficult in PEA-based perovskite, which has a triclinic crystal structure and is less symmetrical as compared to the BA based perovskite orthorhombic structure as well as the tetragonal structure of the 3D perovskite. The knowledge offered by this work is crucial for creating perovskite devices that can endure mechanical deformations.